A Calsequestrin-1 Mutation Associated with a Skeletal Muscle Disease Alters Sarcoplasmic Ca(2+) Release - D’Adamo, Maria Cristina (PLoS One, 2016)
An autosomal dominant protein aggregate myopathy, characterized by high plasma creatine kinase and calsequestrin-1 (CASQ1) accumulation in skeletal muscle, has been recently associated with a missense mutation in CASQ1 gene. The mutation replaces an evolutionarily-conserved aspartic acid with glycine at position 244 (p.D244G) of CASQ1, the main sarcoplasmic reticulum (SR) Ca(2+) binding and storage protein localized at the terminal cisternae of skeletal muscle cells. Here, immunocytochemical analysis of myotubes, differentiated from muscle-derived primary myoblasts, shows that sarcoplasmic vacuolar aggregations positive for CASQ1 are significantly larger in CASQ1-mutated cells than control cells. A strong co-immuno staining of both RyR1 and CASQ1 was also noted in the vacuoles of myotubes and muscle biopsies derived from patients. Electrophysiological recordings and sarcoplasmic Ca(2+) measurements provide evidence for less Ca(2+) release from the SR of mutated myotubes when compared to that of controls. These findings further clarify the pathogenic nature of the p.D244G variant and point out defects in sarcoplasmic Ca(2+) homeostasis as a mechanism underlying this human disease, which could be distinctly classified as “CASQ1-couplonopathy”.